A fresh study for dynamic behaviour of atomic force microscope cantilever by considering different immersion environments. Issue 1 (1st January 2020) - Gholizadeh Pasha, Ali Hossein; Sadeghi, Ali
Abstract: In this article, the dynamic behaviour of a rectangular atomic force microscope immersed in different liquids has been investigated. To account the rotatory inertia and shear deformation effects, Timoshenko beam theory has been applied. Here carbon tetrachloride (CCl4 ), methanol, acetone, water and air have been considered as the environments. Euler–Bernoulli and Timoshenko beam theories has been evaluated for a sample beam. Based on the final results, resonant frequency and amplitude of frequency response functions (FRF) of vertical and rotational displacements reduce by increasing the liquid viscosity also beam length and width. By increasing the beam thickness, the resonant frequency and amplitude of FRF of vertical and rotational displacements increase. For sample, experimental work has been done and compared with theoretical modelling. Results show good agreement.